WHO STEPS-wise Approach in Assessment of Tooth Decay and Children's Quality of Life in Indonesia - Susilawati, Sri; Monica, Grace; Fadilah, R. Putri N; Hanum, Farichah (Makara Journal of Health Research, 2018)
Background: The high prevalence of tooth decay is a major oral health problem in Indonesia. We aimed to determine the relationship between tooth decay and quality of life in children living in rural and urban areas in Indonesia. Methods: A pilot survey was carried out with 2550 students in rural, peri-urban and urban sites in 14 provinces in Indonesia. Age groups included 6-7 years old and 11-12 years old, and we used the pathfinder survey technique. Data collected were based on the WHO STEPS-wise framework using a dental examination by the WHO form (Annex 7) and quality of life questionnaire (Annex 8, Q10). Results: Tooth decay prevalence in 6-7 years old was 88.01%, and 70.27% in the 11-12 years old age group. Children aged 6-7 years old was reported that tooth decay affected their appearance (p=0.013), caused them to avoid smiling and laughing (p=0.003), caused other children to make fun of their teeth (p=0.002) and caused them to miss school hours (p=0.005). Among 11-12 years old children, tooth decay reportedly affected their appearance (p=0.001), caused them to avoid smiling and laughing (p=0.041) and caused them to have chewing difficulty chewing (p=0.031). Conclusions: Tooth decay affects children's quality of life, especially with regard to psychological health.